(untitled) (Journal of the College of Basic Education, 2023)
The terminology and linguistic derivations indicative of the forms of art and the unity of their intellectual and philosophical characteristics fall within the context of the critical effort that searches for an explanation of aesthetic phenomena and achievements and tries to identify the determinants, motives and intellectual foundations associated with them. The existence of patterns and forms that differ from the recognized artistic trends, and that the importance of the current research comes from identifying the nature of intellectual transformations and their impact on artistic production (postmodern drawings), which is a benefit for students of faculties and institutes of fine arts to know the impact of intellectual transformations on the arts, especially the art of drawing. The aim of the research is to identify the impact of intellectual transformations on postmodern arts - the drawing works of the students of the Institute of Fine Arts / Diyala - as a model. One of the conclusions of the study was that most postmodern art works focused on the artistic form at the expense of the idea or content, and the wave of postmodern art came as a reaction to the previous art schools and was influenced by contemporary theories such as Dadaism, surrealism and conceptualism. Therefore, the researcher suggests developing vocabulary in my subjects (aesthetics and art history) that focus on contemporary artistic trends and comparison with previous art schools